Upaya Peningkatan Motorik Halus Melalui Kegiatan Melipat Kertaskertas Pada Anak Kelompok B Di TK Tunas Bangsa Kedungwaru Kecamatan Kunduran Kabupaten Blora Tahun 2015 - HANDAYANI, PUJI; , Dr. Darsinah, M. Si (2015)
This research aims to improve fine motor children in group B in kindergarten Tunas Bangsa Kedungwaru, type of research is classroom action research, while the subject of this study all the students in group B TK Tunas Bangsa Kedungwaru Year 2015/2016, the data collection method in this research document in the form of child the results of paper folding child's activities conducted on the initial conditions and the condition of the end of the first cycle and the second cycle which consists of material learning activities. Research acquired before held improvement Pre-class children who complete cycle of (25%), after increasing research conducted in the first cycle children who are able to fold without the aid increase to 60%. because the results have not been reached or exceeded an indicator of success, then the researchers make improvements back on the second cycle and the result is a child who can fold the paper increases. For children who are able 85%, the results exceeded the indicator of success is 80%. The conclusion of this study successfully. This success is due to the learning methods demonstration and media used by teachers varied.